2015
DOI: 10.1155/2015/724032
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management of the Patient with Maxillofacial Trauma: Review of the Literature and Suggested Clinical Approach

Abstract: According to the Advanced Trauma Life Support recommendations for managing patients with life-threatening injuries, securing the airway is the first task of a primary caregiver. Airway management of patients with maxillofacial trauma is complex and crucial because it can dictate a patient's survival. Securing the airway of patients with maxillofacial trauma is often extremely difficult because the trauma involves the patient's airway and their breathing is compromised. In these patients, mask ventilation and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 65 publications
0
60
0
4
Order By: Relevance
“…Airway stabilisation with adequate pulmonary mechanics is the cornerstone of management in these patients [6]. Pre-oxygenation should be mandatory in these patients, as most of these cases are warranted difficult airway [7]. Effective pre-oxygenation of lungs gives an extra time in the management of airway by increasing oxygen content and Functional Residual Capacity which is the principal store of oxygen during apnoea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Airway stabilisation with adequate pulmonary mechanics is the cornerstone of management in these patients [6]. Pre-oxygenation should be mandatory in these patients, as most of these cases are warranted difficult airway [7]. Effective pre-oxygenation of lungs gives an extra time in the management of airway by increasing oxygen content and Functional Residual Capacity which is the principal store of oxygen during apnoea.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were considered to be full stomach because digestion stops when trauma occurred [7]. As these patients bleed from upper airway, blood is swallowed and accumulated in stomach, therefore risk of regurgitation and aspiration is high.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports on difficulties in the airway management of patients with maxillofacial trauma (3,4). One study found that difficult intubation occurred in 6 of 18 (33%) patients who underwent maxillofacial surgery and previous major head and neck surgeries (1).…”
Section: Discussionmentioning
confidence: 99%
“…Son yıllarda savaş ve terör yaralanmalarında koruyucu ekipmanların diğer vücut bölglerini iyi korumasından kaynaklı penetran yüz ve boyun yaralanma insidansı artmıştır (4,10,11) . Bu yaralanmalardaki hava yolu yönetimine yönelik her bir teknikte avantaj ve dezavantajlar vardır.…”
Section: Hava Yolu Güvenliğiunclassified
“…Mutiple yaklaşımların yanı sıra önerilen rehberlerin izlenmesi önemlidir (2) . Standart monitörizasyon ile (özellikle ETCO 2 ) hasta izlenmelidir, preoksijenasyon mutlaka uygulanmalı, hava yolu optimizasyonunu için bilinçli hastanın en rahat pozisyon almasına izin vermeli, bilinci yerinde olmayan hastalarda çenelerin itilmesi (Jawthrust) manevrası ile hava yolu açıklığı sağ-lanmalıdır (4)(5)(6)(7)(8)(9)(10)(11)(12) . Penetran boyun yaralanmaları olan stabil hastalarda tomografi ilk seçenek olarak düşü-nülmeli ve yaralanmanın durumu ortaya konmalıdır.…”
Section: Hava Yolu Güvenliğiunclassified